Significant damages of core diamond bits in the process of rocks drilling. (January 2016) - Flegner, Patrik; Kačur, Ján; Durdán, Milan; Laciak, Marek; Stehlíková, Beáta; Pástor, Marcel
Abstract: Technology of rotary drilling with diamond bits requires expert knowledge and experience. Drilling modes i.e. combination of pressure on the bit, the rotational speed of the bit, and the quantity and quality of lavage has a decisive influence to achieve maximum drilling speed with minimum consumption drilling bits with diamonds. Optimal setting of the operating mode of technological parameters pressure force, speed and lavage is a fundamental prerequisite to achieving maximum productivity and overall streamlining of the drilling. When talking about the use of diamond bits the careful handling is necessary since assembly operations till drilling process. The shedding of diamonds from the cutting rim and related premature wear, destruction of the entire drilling tool results in inefficient drilling and high cost of labor and drilling tools. This paper deals with the dynamic faults of diamond core bits in drilling of selected rock. We analyze the causes and consequences of developing these faults. The frequency spectra of vibro-acoustic signal of drilling tool with water flush, without water flush, with the bit for drilling of the rock and without bit no-load are presented. Obtained knowledge about the failure causes contributes to the prediction of possible emergency conditions, to the prevention of the operating mode faulty setting. The paper points out possibilities for efficient use of the drilling process from both energetic and economic point of view. Highlights: Experimental measurements of pressure force to the bit and speed of revolutions Frequency spectra of vibro-acoustic speech of drilling tool with the bit and without bit Causes and consequences of non-compliance working procedure when drilling Analysis of damage diamond bit